2007
DOI: 10.1002/cncr.22690
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence in situ hybridization of ductal lavage samples identifies malignant phenotypes from cytologically normal cells in women with breast cancer

Abstract: BACKGROUND. Ductal lavage (DL) does not routinely identify cytologically malignant cells. For this study, the authors asked whether molecular analyses of DL specimens from women with cancer would identify abnormal cells, even if they appeared cytologically normal. METHODS. DL was performed and yielded fluid in 29 of 45 consenting women who were undergoing breast cancer surgery. Array comparative genomic hybridization (CGH) was performed on the corresponding tumor tissue from 14 women. There was no single, comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In fact, prior publications with higher rates of suspicious or malignant cells contained greater percentages of women with DCIS. 21,23 At least 2 groups have shown that random FNA (rFNA) is associated with greater success with respect to cellular adequacy and cell yield. 24,25 Ozanne and Esserman 26 have demonstrated that rFNA is less costly than DL while others have shown rFNA to be very tolerable.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, prior publications with higher rates of suspicious or malignant cells contained greater percentages of women with DCIS. 21,23 At least 2 groups have shown that random FNA (rFNA) is associated with greater success with respect to cellular adequacy and cell yield. 24,25 Ozanne and Esserman 26 have demonstrated that rFNA is less costly than DL while others have shown rFNA to be very tolerable.…”
Section: Discussionmentioning
confidence: 99%
“…Although only 11% of cytology samples were characterized as malignant, 55% of samples showed biomarker changes that were identical to those found in the primary surgical specimen. This study clearly demonstrated the increased sensitivity of molecular probes over cytology for detection of malignancy in ductal lavage samples [32]. …”
Section: Intraductal Lavagementioning
confidence: 84%
“…The authors concluded that FISH-based detection of chromosomal aneuploidy could potentially be used as an adjunct to cytologic evaluation in confirming both benign and malignant diagnoses [31]. Adduci et al [32] utilized array-based comparative genomic hybridization (CGH) in primary surgical specimens then tested matched ductal lavage specimens with region-specific FISH probes to determine whether similar chromosomal alterations were present in both specimens. Although only 11% of cytology samples were characterized as malignant, 55% of samples showed biomarker changes that were identical to those found in the primary surgical specimen.…”
Section: Intraductal Lavagementioning
confidence: 99%
“…A sufficient amount of RNA can be made available from RPFNA samples for quantitative polymerase chain reaction (PCR) for 6 to 12 biomarkers [103] Recently, it has been shown that quantitative evaluation of DNA hypermethylation using methylation-specific PCR can be readily preformed on NAF and DL samples [104] These authors observed that methylation of CCND-2, p16, RAR-beta, and RASSF-1a was significantly more prevalent in tumor than in normal tissue specimens. In another study, using fluorescent in situ hybridization, chromosomal alterations identified in DL specimens obtained from women who underwent breast cancer surgery matched those identified in the corresponding resected breast cancers using comparative genomic hybridization [105]. Interestingly, only 10% of the DL samples were identified as malignant cytologically, whereas over half of the DL samples showed molecular changes characteristic of the tumor.…”
Section: Molecular Analysis and Breast Cytologymentioning
confidence: 95%